Edukasi Pubertas, Menstruasi, dan Perawatan Diri pada Remaja Awal di Sekolah Dasar - Siti Fatimah; Esti Nur Janah; Putri Dwi Kamala; Alma Thania Khusna (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Puberty is an important period in the development of young girls, marked by various physical, emotional, and social changes. A lack of understanding about puberty and menstruation often leads to feelings of anxiety, shame, and poor hygiene practices. Therefore, early education is essential to help female students recognize their body changes and maintain reproductive health properly. This community service was conducted at MI Tamrinussibyan 1 Al Hikmah Benda, specifically targeting early adolescent female students. The activity was carried out through interactive counseling and group discussions, supported by presentation media and illustrations. The topics covered included an introduction to puberty, understanding menstruation, healthy eating habits, and practices for maintaining personal hygiene and reproductive health. The results showed an improvement in the students' understanding of reproductive health, accompanied by a positive change in their attitudes toward self-care during menstruation. This program is expected to provide essential knowledge for students to navigate puberty in a healthy, clean, and confident manner.